Takayasu's disease presenting with tubercular empyema: A rare presentation of a rare disease - Neha Gajanan Phate; Sourya Acharya; Samarth Shukla; Sunil Kumar; Pankaj Jawahar Banode (Journal of the Scientific Society, 2023)
Takayasu's disease (TD) also known as pulseless disease is an arteriopathy characterized by vasculitis affecting the aorta and its branches. It is also known as aortic arch syndrome, nonspecific aorto-arteritis, and young female arteritis. Pulmonary artery involvement in Takayasu's arteritis is a rare phenomenon. Pulmonary artery vasculitis leads to pulmonary arterial hypertension and rarely manifests as pleural effusion. Patients with pulmonary arteritis and pleural effusion usually present as chest pain, cough, and dyspnea. Percentage of involvement of pulmonary artery in TD is variable. Pleural effusion occurs as sequelae of pulmonary artery involvement. We report the case of a 46-year-old female who presented to us with fever, weight loss, dyspnea, and chest pain. Clinical examination and investigations revealed Takayasu's arteritis and tubercular empyema. This case report is a rare presentation of Takayasu's arteritis with tubercular empyema without pulmonary arteritis.